A Quantitative Study of a Drug Treatment Court in a Western Canadian City: Post-sentencing and Reoffence Outcomes - Weinrath, Michael (Canadian journal of criminology and criminal justice, 2019)
Drug treatment courts (DTCs) have been proposed as an alternative to custody that will better deal with drug-dependent offenders through application of therapeutic jurisprudence (TJ). While DTC proponents emphasize the positive aspects of the judicial involvement and intense treatment that most courts provide, critics observe that there are many punitive aspects to DTCs. Frequent court appearances, curfews, urinalysis, multiple bail conditions, and delayed sentencing can be viewed as extensions of coercive social control rather than as benevolent measures intended to help offenders. Further, critics of Canadian DTCs have challenged the efficacy of treatment. This paper seeks to add to a limited Canadian research literature by examining a DTC in the Prairie city of Winnipeg, Manitoba. Two samples are used: sample 1 examines sentencing outcomes and reoffence data for 199 DTC admissions from 2006 to 2014; sample 2 is employed for a quasi-experimental comparative recidivism study using a propensity score matching determined sample of 63 DTC cases with 167 adult probationers from 2010-12. Graduates showed lower rates of reoffence compared to unsuccessful cases. Sentencing outcomes showed that unsuccessful participants were most often incarcerated when re-sentenced on original charges. Probation cases reoffended at higher rates than the matched DTC group. Administrative violations were still higher than in the probation group, and may actually result in an inflated reoffence rate for Canadian DTCs. Policy implications and directions for further research are discussed.